The Same of Beauty of Vision: The Common Research of Photography and Painting - Xiaobing Hu; Fang Tong (SIASAT, 2021)
Photography is the use of view frames to leave a moment of beauty; art is to show the beauty of things on the canvas. Both reflect beauty, bearing the artistic beauty of things, they have a very close relationship. Photography and painting need to be carefully observed from the object of expression, and then from the composition, color, lighting and other aspects to express the main body. This is not only a skill, but also requires the author to have his own unique ideas, thinking and unique vision, so as to use the author's "window of the mind" to find something special to resonate with the viewer.